Influence of natural and anthropogenic factors on the chemical composition of shallow groundwater in the city of Wrocław, south-west Poland - Trałka, Marta; Błachowicz, Marek; Buczyński, Sebastian (Geologos, 2022)
Seen in the light of increasing anthropogenic impacts on the environment and a growing demand for potable water, pollution of groundwater is a very important issue, especially in large city areas. The present research includes analyses of the chemical composition at 109 measuring points in the Wrocław area, and of the spatial distribution of groundwater components with regard to land use, geological structure and hydrogeological conditions. Based on spatial analyses, it has been noted that changes depend mainly on land use and the kind of activity carried out in close proximity of water intake. Shallow groundwater in Wrocław is characterised by a great variability of main components. Factor analysis has made it possible to distinguish these components and determine the degree of their influence on the chemical composition of shallow groundwater in the entire study area. The current research demonstrates the high sensitivity of aquifers to pollution and emphasises the role of human activity in levels of groundwater pollution in urban areas.